Słabnące państwo (Świat Idei i Polityki, 2007)
The contemporary state has evolved from the ancient Greek Polic and Roman civitas through the latter transformations of feudal state. At present due to the progressing globalization the state has been weakened and has been losing some of its vital functions and prerogatives. Some of those functions have been taken over by the transnational corporations and the international organizations such as the World Trade Organization and International Monetary Fund. The decline of the contemporary state is also reflected in its inability to fulfill the aspirations of its citizens and to defend effectively the interests of the nation.There are various definitions and concepts of the desired role of the state. All of them shape a highly idealistic picture of the state which is incompatible with the existing reality.There also are some controversies over the tasks,which the shate should perform vis a vis the market as well as to what extent the state power should be decentralized or centralized.There are also discussions whether the state should be weak or strong. The fact is that an increasing number of the contemporary states are on the brink of bankruptcy. This paper tries to explain the reasons why some states are declining dechining and what should be done in order to stop that decline.